Pré-dimensionamento de uma bacia de detenção para controle de águas pluviais na cidade de Fortaleza/Ce. - Rolim, Larissa Zaira Rafael (2017)
The increased waterproofing of urban river basins, due to the growth of the city, generates direct impacts such as floods. It is proposed the implementation of a compensatory technique in the city of Fortaleza as an alternative to the hygienist technique commonly used in the city, differing from the hygienist model because it manages pluvial management and urban planning at the same time. Thus, a methodology with specific parameters is applied in Fortaleza, which consists in the pre-dimensioning of the detention basin with the aid of the IDF curve, in the Talbot formulation, as input rainfall. Inflows to the control device are provided by the rational method and the output volumes follows a constant launch rates in the rainwater network. With the aid of the city's planialtimetric plants, the hydrological parameters were determined for the pre-dimensioning of the detention basin, assessing its technical and economic viability. In the simulations described in the work, the proposed control device presented reasonable contributions for the reduction of flow in the area, providing favorable conclusions regarding its operation and feasibility.